Cell Secretion: Current Structural and Biochemical Insights. (2010) - Trikha, Saurabh; Lee, Elizabeth C.; M. Jeremic, Aleksandar
Abstract : Essential physiological functions in eukaryotic cells, such as release of hormones and digestive enzymes, neurotransmission, and intercellular signaling, are all achieved by cell secretion. In regulated (calcium-dependent) secretion, membrane-bound secretory vesicles dock and transiently fuse with specialized, permanent, plasma membrane structures, called porosomes or fusion pores. Porosomes are supramolecular, cup-shaped lipoprotein structures at the cell plasma membrane that mediate and control the release of vesicle cargo to the outside of the cell. The sizes of porosomes range from 150nm in diameter in acinar cells of the exocrine pancreas to 12nm in neurons. In recent years, significant progress has been made in our understanding of the porosome and the cellular activities required for cell secretion, such as membrane fusion and swelling of secretory vesicles. The discovery of the porosome complex and the molecular mechanism of cell secretion are summarized in this article.